FACTORS AFFECTING POVERTY RATE IN INDONESIA 2015-2019 - Sitti Retno Faridatussalam; Althofa Khoironi (Prosiding University Research Colloquium, 2022)
Poverty is a complex problem that exists in Indonesia. Indonesia's poverty in 2016-2019 fluctuated. This study aims to determine the effect of Economic Growth, Human Development Index, and Internet Access on Poverty by using the Least Square Dummy Variable (LSDV) approach. Based on the results of panel data analysis from this study, it shows that economic growth has no effect on poverty in Indonesia. Meanwhile, HDI and Internet Access have an effect on Poverty in Indonesia. The government should increase the development of regional facilities, create more adequate job opportunities, increase the provision of scholarships, supervise industries and increase public awareness about the importance of education.